Complex use of cycleand power-ergometry in determining the physical working capacity of young athletes - M. F. Khoroshukha; M. M. Filippov; A. I. Bosenko; Ye. L. Mykhaliuk; O. Yu. Buriak (Сучасні медичні технології)
The aim of this study is to scientifically substantiate the possibilities of complex use of cycle- and power-ergometry in determining aerobic and anaerobic-aerobic performance of power nature.